BASH-GN: a new machine learning–derived questionnaire for screening obstructive sleep apnea - Huo, Jiayan; Quan, Stuart F.; Roveda, Janet; Li, Ao (Sleep & breathing, 2023)
Purpose This study aimed to develop a machine learning–based questionnaire (BASH-GN) to classify obstructive sleep apnea (OSA) risk by considering risk factor subtypes. Methods Participants who met study inclusion criteria were selected from the Sleep Heart Health Study Visit 1 (SHHS 1) database. Other participants from the Wisconsin Sleep Cohort (WSC) served as an independent test dataset. Participants with an apnea hypopnea index (AHI) ≥ 15/h were considered as high risk for OSA. Potential risk factors were ranked using mutual information between each factor and the AHI, and only the top 50% were selected. We classified the subjects into 2 different groups, low and high phenotype groups, according to their risk scores. We then developed the BASH-GN, a machine learning–based questionnaire that consists of two logistic regression classifiers for the 2 different subtypes of OSA risk prediction. Results We evaluated the BASH-GN on the SHHS 1 test set ( n = 1237) and WSC set ( n = 1120) and compared its performance with four commonly used OSA screening questionnaires, the Four-Variable, Epworth Sleepiness Scale, Berlin, and STOP-BANG. The model outperformed these questionnaires on both test sets regarding the area under the receiver operating characteristic (AUROC) and the area under the precision-recall curve (AUPRC). The model achieved AUROC (SHHS 1: 0.78, WSC: 0.76) and AUPRC (SHHS 1: 0.72, WSC: 0.74), respectively. The questionnaire is available at https://c2ship.org/bash-gn . Conclusion Considering OSA subtypes when evaluating OSA risk may improve the accuracy of OSA screening.